Organic Waste Management Into Compost Fertilizer as a Form of Socialization and Practical Activities in Class 3 of SDN Keleyan 1t Fertilizer As A Form Of Socialization And Practical Activities In Class 3 Of SDN Keleyan 1 - Umam, Zainul; Saputra, Ilham Widiyanto; Wardah, Fika Reihah; Fadlillah, M. (Edumedia Solution, 2026)
The problem of organic waste in the school environment, particularly at SDN Keleyan 1, remains a challenge in creating a clean and healthy environment. The large amount of organic waste generated daily, such as food scraps and leaves, is not managed properly, thus potentially polluting the surrounding environment. One solution that can be implemented is processing organic waste into compost, which not only provides ecological benefits but can also be used as an educational tool for students. This article aims to describe practical and educational activities in processing organic waste into compost in grade 3 of SDN Keleyan 1. Through an approach involving socialization, demonstrations, and direct mentoring, students are encouraged to understand and practice the process of processing organic waste in a simple and effective way. The results of the implementation of the activity showed an increase in students' knowledge and skills in processing organic waste into compost independently. In addition, this activity also succeeded in building students' awareness of the importance of maintaining a clean environment and the sustainability of the school ecosystem. Overall, this activity has proven effective in educating students about organic waste management and introducing the concept of environmental sustainability from an early age, thereby creating a cleaner, healthier, and environmentally conscious school environment